Ceprotan Performing Art: A Traditional Folkart Based on Urband Legend (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
Traditional arts of born and develops from urban society by keeping a manifestation of its and forms are different in the regions. Ceprotan as a traditional arts from Sekar Village, Donorojo Sub-district, Pacitan Regency. Form of this research is qualitative descriptive with focused to describe and explain about Ceprotan performing art in Sekar Village, that source from the local history, that is the story of Ki Godeg and Dewi Sekar. Research object are Ceprotan performing art which held once a year, in Senin Kliwon days, in Dulqokdah month. Data collected technique using observation, noted, and content analysis. Result of research find that Ceprotan is a traditional art performed same time with Bersih Desa ceremony in Sekar Village society. Ceprotan perforiming art held once a year, only in day of Senin Kliwon, month of Dulqokdah in Lunar calendar. Ceprotan performing art performed the sendratari (dramatic dancing art) telling the story of Ki Godeg and Dewi Sekar journies with develop the Sekar Village. In the end of performing, done attraction throwing the young coconuts from some of young people from Sekar Village.